Increased Axonal Regeneration and Swellings in Intraepidermal Nerve Fibers Characterize Painful Phenotypes of Diabetic Neuropathy - Cheng, Hsinlin T; Dauch, Jacqueline R; Porzio, Michael T; Yanik, Brandon M; Hsieh, Wilson; Smith, A.Gordon; Singleton, J.Robinson; Feldman, Eva L (The journal of pain, 2013)
Abstract We examined changes in intraepidermal nerve fibers (IENFs) to differentiate patients with diabetic neuropathy (DN) and diabetic neuropathic pain (DN-P) from those with DN without pain (DN-NOP). Punch skin biopsies were collected from the proximal thigh (PT) and distal leg (DL) of normal subjects, patients with type 2 diabetes without evidence of DN (DM), or DN-P and DN-NOP patients. Protein gene product 9.5-positive (PGP+) immunohistochemistry was used to quantify total IENF, and growth-associated protein 43 (GAP43) for regenerating IENF. Compared to normal subjects and patients with type 2 diabetes without evidence of DN, both DN-P and DN-NOP have reduced PGP+ IENF densities in DL and PT. Although GAP43+ IENF densities were also reduced in DL for both DN-P and DN-NOP, the GAP43+ IENF densities in PT of DN-P remained at the control levels. Higher GAP43/PGP ratios were detected in DN-P compared to DN-NOP in the DL and PT. In parallel, increased numbers of axonal swellings per PGP+ fiber (axonal swelling/PGP) were detected in DN-P compared to normal subjects, patients with type 2 diabetes without evidence of DN, and DN-NOP in the DL. These axonal swellings were positive for tropomyosin-receptor-kinase A and substance P, suggesting that they are associated with nociception. Perspective Among patients with DN, the ratios of GAP43/PGP and axonal swelling/PGP are likely to differentiate painful from painless phenotypes.